2013
DOI: 10.1364/ao.52.004582
|View full text |Cite
|
Sign up to set email alerts
|

Snapshot 2D tomography via coded aperture x-ray scatter imaging

Abstract: This paper describes a fan beam coded aperture x-ray scatter imaging system which acquires a tomographic image from each snapshot. This technique exploits cylindrical symmetry of the scattering cross section to avoid the scanning motion typically required by projection tomography. We use a coded aperture with a harmonic dependence to determine range, and a shift code to determine cross-range. Here we use a forward-scatter configuration to image 2D objects and use serial exposures to acquire tomographic video o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Transmittance is the quantity of energy that passes through an object, for this case, it is the magnitude that expresses the quantity of X-ray light that is definitely projected over an object [20]. The coded apertures have been developed and tested on X-ray systems based on fan beam geometry [21]. The coded pattern is modeled in Matlab, a mold of the aperture is printed and is filled with Tungsten powder and it is sealed with epoxy resin.…”
Section: Coded Aperture Designmentioning
confidence: 99%
“…Transmittance is the quantity of energy that passes through an object, for this case, it is the magnitude that expresses the quantity of X-ray light that is definitely projected over an object [20]. The coded apertures have been developed and tested on X-ray systems based on fan beam geometry [21]. The coded pattern is modeled in Matlab, a mold of the aperture is printed and is filled with Tungsten powder and it is sealed with epoxy resin.…”
Section: Coded Aperture Designmentioning
confidence: 99%
“…A Gaussian measurement model is not appropriate for many important applications, including X-ray [9,20] and chemical imaging [29,30,31]. The observed data in these applications are characterized by counts, typically under Poisson statistics.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…The coded aperture modulates the scattered photons in a manner that depends on the position of emission and on the angle of scatter, helping to disambiguate the source of observed photons when seeking to recover f k from y k . Further details on the X-ray system may be found in [9,20].…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…For example, we have shown that 3D hyperspectral [18], diffraction [19], and x-ray scatter [20,21] images may be reconstructed from 2D data. We have also analyzed compressive sampling for reconstruction of 3D objects with conventional optics [22].…”
Section: Introductionmentioning
confidence: 99%